2010
DOI: 10.3945/ajcn.2009.27946
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of lactose malabsorption among healthy southern and northern Indian populations by genetic analysis and lactose hydrogen breath and tolerance tests

Abstract: The frequency and degree of LM is higher in southern than in northern Indian healthy populations because of genetic differences in these populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 46 publications
7
56
0
3
Order By: Relevance
“…This hydrogen meter is widely used and validated for the assessment of SIBO. [28][29][30] Hydrogen gas concentration was expressed in parts per million (ppm) at that instant. After providing a baseline breath sample, the patient ingested 50 g of glucose in 300 mL of water.…”
Section: Glucose Hydrogen Breath Testmentioning
confidence: 99%
“…This hydrogen meter is widely used and validated for the assessment of SIBO. [28][29][30] Hydrogen gas concentration was expressed in parts per million (ppm) at that instant. After providing a baseline breath sample, the patient ingested 50 g of glucose in 300 mL of water.…”
Section: Glucose Hydrogen Breath Testmentioning
confidence: 99%
“…However controversial results [16] are available in which it was observed that patients with diarrheal type of IBS (44 %) have a higher incidence of LI as compared to spastic type (28 %) as well as patients with features of both types (28 %). Moreover, frequency and degree of lactose malabsorption was high in southern than in northern Indian healthy populations due to genetic differences in these populations [17].…”
Section: Lactose Intolerance (Li)/malabsorptionmentioning
confidence: 97%
“…A prevalência Tabela 1-Prevalência de hipolactasia primária do adulto em diferentes populações Local Prevalência (%) Método Alemanha 35 14,8 Hidrogênio Expirado Áustria 36 20,1 Hidrogênio Expirado Brasil (brancos) 37 57 genético Brasil (crianças índias Terenas) 38 89,3 após 4 anos Hidrogênio Expirado Brasil (japoneses) 37 100 genético Brasil (mulatos) 37 57 genético Brasil (negros) 37 80 genético China (Norte) 39 87,3 genético Estônia (ligados aos finlandeses) 40 24,8 genético França 41 23,4 Hidrogênio Expirado Hungria 26 37 genético Índia (Norte) 42 67,5 genético Índia (sul) 42 86,8 genético Itália 43 51(Norte) 71(Sicilia) Hidrogênio Expirado Japão (adultos) 44 89 Hidrogênio Expirado Jordânia (beduínos) 45 24 Hidrogênio Expirado Jordânia (oeste) e Palestina 45 75 Hidrogênio Expirado Russia (Nordeste) 46 35,6 genético Sibéria (oeste, nativos Khants) 47 94 Tolerância/ glicemia Somalis 48 76 Hidrogênio Expirado Sudão (tribo Béja, pecuaristas) 49 16,8 Hidrogênio Expirado Sudão (tribo Nilotes, agricultores) 49 74,5 Hidrogênio Expirado Suécia (crianças caucasianas) 50 10 genético Suécia (crianças não-caucasianas) 50 66 genético Suécia (idoso caucasiano) 50 5 genético Tuaregues 51 12,7 Hidrogênio Expirado Turquia 52 71,3 Hidrogênio Expirado da hipolactasia vai aumentando na direção do centro-sul da Europa para chegar próximo aos 100% na Ásia e Oriente Médio. 53 Na África, com diferentes variantes alélicas, o genótipo de lactasia persistente foi mais frequente nos povos com tradição de pecuária em relação aos agricultores 28 .…”
Section: Epidemiologiaunclassified